2013
DOI: 10.7762/cnr.2013.2.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Weight Status and Dietary Factors Associated with Sugar-Sweetened Beverage Intake among Korean Children and Adolescents - Korea National Health and Nutrition Examination Survey, 2008-2011

Abstract: There has been growing concern about the role of sugar-sweetened beverages (SSBs) in the development of obesity. This study investigated factors associated with SSB intake among Korean children (7-12 years) and adolescents (13-18 years). We examined associations between SSB intake and demographic and dietary factors using nationally representative data from the 2008-2011 Korea National Health and Nutrition Examination Survey, and 3,179 children and 2,242 adolescents were included in the final analysis. We calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
(17 reference statements)
3
20
0
Order By: Relevance
“…In terms of different dietary practices in Asia, the mixed findings regarding the relationship between SSBs and obesity can be, in part, explained. SSB drinkers consumed more total energy and showed a higher prevalence of obesity in Chinese children [ 14 ] and Korean boys 7–12 years of age [ 33 ]. Conversely, sugar intake from SSBs and snacks was not significantly associated with weight status in Japanese and Cambodian children [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of different dietary practices in Asia, the mixed findings regarding the relationship between SSBs and obesity can be, in part, explained. SSB drinkers consumed more total energy and showed a higher prevalence of obesity in Chinese children [ 14 ] and Korean boys 7–12 years of age [ 33 ]. Conversely, sugar intake from SSBs and snacks was not significantly associated with weight status in Japanese and Cambodian children [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Canadian adolescents 9–18 years of age consumed more added sugars; conversely, children 1–8 years of age consumed sugars from natural food sources [ 40 ]. Lee et al [ 33 ] reported that SSB intake was inversely associated with milk, fruit and vegetable intake in Korean children and adolescents. Our additional analysis showed lower sugar intake from milk and fruits and higher sugar intake from processed foods in subjects 12–14 years of age compared to those 9–11 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome variable was a dichotomous indicator of the consumption of at least one sugar sweetened beverage (SSB) per day as compared to less than one SSB per day. Drinking over one SSB per day has been associated with individuals' health status in several recent studies [ 35 , 48 , 49 ]. SSB was measured by consumption of fruit flavored drinks, regular soft drinks, slush, sport drinks, and energy drinks on a 5-point scale ranging from never to several times per day (100% fruit juice was excluded).…”
Section: Methodsmentioning
confidence: 99%
“…Both high ED diets and high intakes of caloric beverages have been reported to be associated with high energy intakes and were suggested to be associated with childhood obesity. 45 When using ED F&B calculation method (including caloric beverages), this association seems to be contradictive as high intakes of caloric beverages reduced the ED F&B value, owing to their relatively high water content. The inclusion of caloric beverages in the ED calculation may consequently attenuate or even reverse the expected positive association between ED and weight status.…”
Section: Study Characteristicsmentioning
confidence: 99%